Exergy evaluation and ORC use as an alternative for efficiency improvement in a CI-engine power plant. (December 2018) - da Silva, Julio A.M.; Seifert, Vitor; de Morais, Vinícius O.B.; Tsolakis, Athanasios; Herreros, Jose; Torres, Ednildo
Abstract: The search for efficient processes in order to reduce the dependence on fossil fuels and to mitigate pollutants emission is mandatory in current society. Exergy analysis provides a clear indication of where efforts should be concentrated in the search for more efficient processes. Once the processes responsible for main exergy destruction are revealed, new technologies can be used to decrease the entropy generation so that the efficiency of the process is increased. In this paper a Brazilian power plant with installed capacity of 300 MW using turbo-aspirated compression ignition (CI) engines is investigated. Results reveal that although about 29% of energy input is sent to environment from low and high temperature cooling systems, it represents only 2% in exergy terms. Furthermore, results show that the highest exergy destruction, 44%, happens inside the engine and it is unavoidable considering the used technology. The exergy of exhaust gases represents about 6.5% of the exergy input and can be recovered for power generation. The use of an organic Rankine cycle (ORC) optimized in respect to working fluid, operation conditions and configuration can recover 45% of the exhaust gases exergy increasing the overall fuel to electricity energy efficiency of the plant from 43.1% to 46.2%.